Dephosphorylation and biodistribution of 1‐13C‐phospholactate in vivo. (3rd July 2014) - Shchepin, Roman V.; Pham, Wellington; Chekmenev, Eduard Y.
<x xml:space="preserve">Abstract</x> Here, we present a new approach for the delivery of a metabolic contrast agent for in vivo molecular imaging. The use of a phosphate‐protecting group that facilitates parahydrogen‐induced polarization of 1‐13C‐phospholactate potentially enables the in vivo administration of a hydrogenated hyperpolarized adduct. When injected, nonhyperpolarized 1‐13C‐phospholactate is retained in the vasculature during its metabolic conversion to 1‐13C‐lactate by blood phosphatases as demonstrated here using a mucin 1 mouse model of breast cancer and ex vivo high‐resolution 13C NMR. This multisecond process is a suitable mechanism for the delivery of relatively short‐lived 13C and potentially 15N hyperpolarized contrast agents using –OH phosphorylated small molecules, which is demonstrated here for the first time as an example of 1‐13C‐phospholactate. Through this approach, dl‐1‐13C‐lactate is taken up by tissues and organs including the liver, kidneys, brain, heart, and tumors according to a timescale amenable to hyperpolarized magnetic resonance imaging.